HUBUNGAN SIKAP DAN POLA KOMUNIKASI ORANG TUA DENGAN PERILAKU SEKS PRANIKAH PADA SISWA SMA DI KOTA SAMARINDA TAHUN 2015 - Nur Rohmah (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2016)
Base on various reports, stated that many teens already trapped in unhealthy reproductive behavior, including sexual behavior before marriage. Based on the survey results Indonesian Family Planning Association (IPPA) East Kalimantan in 2008. Of the 300 adolescents (aged 13-20 years) 12% of respondents claimed to have had sex. This study aims to determine the relationship Attitudes and Patterns of Communication With Parents with Premarital Sex Behavior in High School Students in Private Samarinda in 2010. This study is observational method "Cross Sectional Study". with a total sample of 102 students. Data were obtained from questionnaires answered. The analysis is the analysis of uni-variate and bi-variate with Chi Square Test. Uni- variate analysis of the data obtained from 102 respondents as much as 3% had sex should husband and wife, and 2% had had sex in the past month and 1% had had sex in a last month . Behavior different sexual risk among respondents as many as 17% of respondents which high risk behavior , and only 5% who do not have risky behaviors. Bi-variate analysis showed an association with the attitude of premarital sexual behavior p = 0.028 and no association with the communication patterns of premarital sexual behavior (p = 0061). This study is expected the cooperation between teachers and parents to provide education and knowledge about good reproductive health in order to fortify the attitude and behavior of Private High School Youth in Samarinda